Antecedents of Smoking Addiction Among University Students - Kamarul Ikwan Kamarulzaman; Mohd Hanif Hakimi Hamidi; Muhammad Irfan Abd Nasir; Asmidar Suhadah Sukeri; Nur Adlina Mohd Izham (Cita Konsultindo Research Center, 2021)
Smoking has been a habit among university students, yet it has received scares empirical research attention. This work is focusing on identifying the factors associated with smoking addiction among university students. The self-administrated questionnaire was distributed to 100 respondents of students in Universiti Kuala Lumpur Business School through an online survey. The data was there analyzed using the SPSS. The result shows that stress, friends, and family are positively related to smoking addiction among the students.